Discharge criteria in the newborn period and problems associated with early discharge [Yenidoǧanda taburculuk kriterleri ve erken taburculuǧa baǧli sorunlar] - (:unkn) unknown (My University, 2007)
In recent years there has been a trend towards earlier discharge of newborns. This can lead to problems such as feeding difficulties, dehydration, jaundice and problems in newborn screening. It has been stated that in early discharged newborns, difficulties associated with lactation are not diagnosed and these newborns are frequently readmitted to hospitals with weight loss or even dehydration. Inadequate calori intake and/or dehydration resulting from problems in breastfeeding could contribute to jaundice. Before discharge all infants should be evaluated for the risk of developing severe hyperbilirubinemia by determining the level of total serum bilirubin and/or transcutanous bilirubin and marking the result on the Bhutani nomogram. Appropriate follow-up should be arranged according to the risk zones. Early discharge of newborns could lead to problems in terms of newborn screening for congenital hypothyroidism and phenylketonuria. After discharge preterms are more freqeuently readmitted to hospitals than term newborns. Pretems who are able to maintain their body temperature at room temperature, has no difficulty in feeding, weighs at least 1600 grams, gains weight and who are free of apnea and bradycardia in the previous week before discharge could be discharged if the parents have the ability to look after their infant. Term infants who are not in intensive care unit could be discharged at 48 hours provided that the infant has no feeding problems, bilirubin levels are not in the high risk zone according to the Bhutani nomogram, samples for newborn screening are obtained and the family are able to take care of the infant. Generally discharge of newborns before 24-36 hours are not recommended as it increases neonatal morbidity and mortality. In case of an early discharge early follow-up should be arranged since readmission rates for these newborns are higher.